The Effect of Organizational Support Perception, Organizational Change, and Organizational Culture on Employee Performance of PT. Pegadaian Malang During COVID-19 - Rizqi Fachriansyah; Uci Yuliati; Dicky Wisnu Usdek Riyanto (Universitas Muhammadiyah Malang, 2021)
The purpose of this study was to determine the effect of perceived organizational support, organizational change, and organizational culture on employee performance. This type of research is explanatory. The populations are 61 employees of PT. Pegadaian (Persero) Malang City, sampling using the census method. This type of data uses quantitative and the data source is primary data. Data collection through questionnaires. The method of analysis uses a range of scales and multiple linear regression. The results of the calculation of the perceived organizational support scale range show high, organizational change shows good, organizational culture shows good and employee performance shows high. Perceptions of organizational support, organizational change, and organizational culture partially and simultaneously have a significant effect on employee performance.